The dark side of Zionism : Israel's quest for security through dominance - Thomas, Baylis, 1932- (Lexington Books, 2009)
The Dark Side of Zionism: Israel's Quest for Security through Dominance arises out of the scholarship of the "new historians," a group of mostly Israeli scholars who have uncovered a history widely ignored in the popular media. Baylis Thomas argues that both the early Zionists and, later, the Israelis sought their security through the military domination of the Indigenous Arab population of Palestine. This strategy required both avoiding negotiations with the Palestinian-Arabs and provoking the weak Arab states-opposed to the Israeli takeover of Palestine-into entering wars they would lose. The